Workshop Lukis Kain Dengan Tema Wayang Beber Pacitan Bagi Siswa SMU?SMK/MA Se-Kabupaten Pacitan Jawa Timur di Sanggar Budaya Jagad Warna Warni - NRA Candra (Institut Seni Indonesia Surakarta, 2016)
Realized that natural attractions which are supported by arts and culture to always increase local revenues, so that the district offices of Pacitan through cultural tourism and sports youth strive to exploit and explore various potential it self. many circles are also involved in accordance with their own competence. Look at that phenomenon, presumably necessary role of education, one of from the higher education institutions contributed to these positive efforts. From community service activities it is necessary to research to see an opportunity that accordance with their competence, then the wayang beber workshop was held and directed against students of senior high school. This workshop activity undertaken in a sustainable manner is considered essential in order to grow awareness and high motivation, especially for the younger generation of Pacitan to always want to know and love the original Pacitan’s Beber Puppet. Key words : Beber Puppet, workshop